Analysis of the Potential and Contribution of the Business Sector in Samarinda City as a Buffer City for IKN - Queena, Cella; Aziza Gaffar, Emmilya Umma (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2025)
This research aims to find out the business sectors that have the potential to be developed further as an effort for Samarinda City to become a Buffer City for IKN. This type of research is quantitative using secondary data derived from the annual report published by BPS. The data used in this study is data time series for 6 years from 2018-2023. The analysis technique used in this study is the analysis Location Quotient (LQ), analysis Shift-Share, and Quadrant analysis processed using Ms. Excel. The results of the study show that there are 14 base business sectors and 3 non-base business sectors and in Samarinda City. And there are 6 business sectors that have the potential to be developed in supporting the development of IKN